2019
DOI: 10.1128/mra.00358-19
|View full text |Cite
|
Sign up to set email alerts
|

Illumina Sequencing Reveals the First Near-Complete Genome Sequence of Ugandan Passiflora Virus

Abstract: Here, we present the first near-complete genome of Ugandan Passiflora virus (UPV) sequenced from a symptomatic sample of KH7 passion fruit (Passiflora edulis Sims) variety. UPV had limited amino acid identity with other potyviruses known to cause passion fruit woodiness disease (PWD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Plant virus diagnostic techniques have evolved with greater adoption of HTS, which involve sequencing of the total nucleic acid followed by bioinformatics (Adams et al, 2009;Maree et al, 2018). HTS has proven to be reliable and highly sensitive for virus detection and discovery (Al Rwahnih et al, 2009;Maina et al, 2016c;Maina et al, 2016d;Maina et al, 2016e;Maina et al, 2017d;Maina et al, 2017e;Maina and Jones, 2017g;Maina et al, 2019b), and when combined with biological information, has successfully resolved many disease complexes in agricultural and horticultural crops around the world (Maree et al, 2018;Wamaitha et al, 2018;Mbeyagala et al, 2019). In plant health diagnostics, the gold standards utilized by plant quarantine programs globally are biological indexing using indicator plants, serology, PCR, and electron microscopy.…”
Section: Overview Of High-throughput Sequencing Approaches In Plant V...mentioning
confidence: 99%
“…Plant virus diagnostic techniques have evolved with greater adoption of HTS, which involve sequencing of the total nucleic acid followed by bioinformatics (Adams et al, 2009;Maree et al, 2018). HTS has proven to be reliable and highly sensitive for virus detection and discovery (Al Rwahnih et al, 2009;Maina et al, 2016c;Maina et al, 2016d;Maina et al, 2016e;Maina et al, 2017d;Maina et al, 2017e;Maina and Jones, 2017g;Maina et al, 2019b), and when combined with biological information, has successfully resolved many disease complexes in agricultural and horticultural crops around the world (Maree et al, 2018;Wamaitha et al, 2018;Mbeyagala et al, 2019). In plant health diagnostics, the gold standards utilized by plant quarantine programs globally are biological indexing using indicator plants, serology, PCR, and electron microscopy.…”
Section: Overview Of High-throughput Sequencing Approaches In Plant V...mentioning
confidence: 99%
“…Later studies, however, found that the causal agent of PWD in Brazil and South Africa is cowpea aphid-borne mosaic virus (CABMV), while that in Japan is East Asian Passiflora virus (EAPV) (Iwai et al 2006). More recently, many other viruses were reported to cause PWD, some of which, like Ugandan passiflora virus, have been shown to be a limiting factor for passionfruit production locally (Ochwo-Ssemakula et al 2011;Mbeyagala et al 2019). Despite their diversity in species and differences in geographical distribution, all PWD-causing viruses are positive-sense RNA viruses belonging to the genus Potyvirus under the family Potyviridae (Lefkowitz et al 2018).…”
Section: Introductionmentioning
confidence: 99%